Male Earnings, Marriageable Men, and Nonmarital Fertility: Evidence from the Fracking Boom - Kearney, Melissa S.; Wilson, Riley (The Review of Economics and Statistics, 2018)
We investigate whether an increase in the potential earnings of men leads to an increase in marriage and a reduction in nonmarital births by exploiting the positive economic shock associated with fracking in the 2000s. A reduced-form analysis reveals that in response to local-area fracking production, which increased wages and jobs for non-college-educated men, both marital and nonmarital birth rates increase, but marriage rates do not. The pattern of results is consistent with positive income effects on births but no associated increase in marriage. We contrast our findings to the Appalachian coal boom experience of the 1970s and 1980s.